Dinner planning and preparation considerations of parents with children attending childcare. (1st January 2023) - Dahl, Alicia A.; Mayfield, Melanie; Fernandez-Borunda, Alejandra; Butts, Shanika Jerger; Grafals, Melanie; Racine, Elizabeth F.
Abstract: The objective of this study was to explore the meal-related thought processes, planning, and purchasing behaviors of primary caregivers on weeknights. A mixed-methods study design was applied using a cross-sectional survey and qualitative interviews. Thirty-three primary caregivers from early childhood education centers were enrolled in the study. Descriptive statistics of sample characteristics were conducted and an a-priori thematic analysis of interview recordings was completed using NVivo Qualitative software. The following key themes were identified: satisfaction with dinner, feeding behaviors before the COVID-19 pandemic, regretful feeding experiences, meal planning, food purchasing, social support, and general feelings about dinner preparation and cooking. Important considerations for food purchasing included family satisfaction, price, convenience, and healthfulness. Satisfaction around dinner choices varied, with dissatisfaction often related to a bad workday, being stressed, or making meals that family members disliked. Findings demonstrate the need for more research and interventions around the topic of meal planning and preparation, specifically for working parents, that further examine tasks required for providing meals, the physical and cognitive time for meal preparation, and helpful means of support.